Enantioselective metabolism of chiral polychlorinated biphenyl 2, 2′, 3, 4, 4′, 5′, 6-Heptachlorobiphenyl (CB183) by human and rat CYP2B subfamilies. (December 2022) - Ito, Terushi; Miwa, Chiharu; Haga, Yuki; Kubo, Makoto; Itoh, Toshimasa; Yamamoto, Keiko; Mise, Shintaro; Goto, Erika; Tsuzuki, Harunobu; Matsumura, Chisato; Nakano, Takeshi; Inui, Hideyuki
Abstract: Chiral polychlorinated biphenyls (PCBs) have atropisomers that have different axial chiralities and exist as racemic mixtures. However, biochemical processes often result in the unequal accumulation of these atropisomers in organisms. This phenomenon leads to enantiospecific toxicity enhancement or reduction because either of the atropisomers mainly affects toxicity expression. Enantioselective accumulation is caused by cytochrome P450 (CYP, P450) monooxygenases, especially the CYP2B subfamilies. Therefore, this study investigates the metabolism of a chiral PCB in vitro . Both atropisomers isolated from racemic 2, 2′, 3, 4, 4′, 5′, 6-heptachlorobiphenyl (CB183) were metabolized by human CYP2B6, but not rat CYP2B1. This may be due to the difference in the size of the substrate-binding cavities of CYP2B6 and CYP2B1. The stable accommodation of (−)-CB183 in the cavity without any steric hindrance explained the preferential metabolism of (−)-CB183 compared to (+)-CB183. Two hydroxylated metabolites, 3′–OH–CB183 and 5-OH-CB183, were identified. The docking study showed that the 3′-position of the trichlorophenyl ring closely approaches the heme of CYP2B6. To our knowledge, this is the first study to elucidate the structural basis of chiral PCB metabolism by P450 isozymes. These results will help promote the precise toxicity evaluation of chiral PCBs and provide an explanation of the structural basis of chiral PCB metabolism. Graphical abstract: Image 1 Highlights: Atropisomers from racemic CB183 were used as substrate in metabolism experiments. Atropisomer-dependent CB183 metabolism by human CYP2B6 was observed. Stable accommodation of CB183 in the CYP2B6 cavity was significant for activity. Vicinity of CB183 to the heme iron was also responsible for the activity.